Maternal factors affecting low birth weight in urban area of Bangladesh - Azimul, SK; Matin, A; Shabnam, JH; Shamianaz, S; Bannerje, M (Journal of Dhaka Medical College, 2010)
Objectives: In Bangladesh low birth weight (LBW) rate is quite high even in urban area. The present study was conducted to determine the maternal factors (e.g. socioeconomic, nutritional and pregnancy related) affecting LBW in urban community of Bangladesh. Methods: This case control study was done at Shaheed Shohrawardy Medical College Hospital, Dhaka. Normally delivered singleton live births babies from January 2003 to January 2005 in obstetrics wards were selected purposively and after enrollment all newborn's birth weight was measured. Then from the total (N=583) study populations child-mother pairs formed and were divided in LBW group (n=135) and normal birth weight (NBW) group (n=448). Maternal socioeconomic, nutritional and pregnancy regarding data (e.g. parity, inter pregnancy interval, number of antenatal visits) were collected and then variables were analyzed to find out maternal factors affecting LBW. Results: The LBW incidence was found 23.2% and mean birth weight was found 2762 gm. More proportion of LBW babies came from the mother of <20year of age group. Significant relationship was found between early maternal age, education, socioeconomic status, anaemia, iron & vitamin supplementation during pregnancy, maternal weight, body mass index (BMI) with LBW. Parity, inter pregnancy interval and number of antenatal visit were also found significant risk factors for LBW. No relationship was found between tobacco use and maternal height with LBW. Conclusion: Among the various epidemiological factors the maternal factors like antenatal care, parity, inter pregnancy interval, iron & vitamin supplementation during pregnancy are found to influence birth weight. Hence, it is the need of the hour to strengthen the existing maternal services at the community level to reduce LBW in Bangladesh. Key words: LBW (Low Birth Weight); NBW (Normal Birth Weight). DOI: 10.3329/jdmc.v18i1.6309 J Dhaka Med Coll. 2009; 18(1) : 64-69